2020
DOI: 10.1111/csp2.243
|View full text |Cite
|
Sign up to set email alerts
|

Risk to North American birds from climate change‐related threats

Abstract: Climate change is a significant threat to biodiversity globally. Here, we assessed the risk to 544 birds in the United States from future climate changerelated threats under a mitigation-dependent global warming scenario of 1.5 C and an unmitigated scenario of 3.0 C. Threats considered included sea level rise, human land cover conversion, and extreme weather events. We identified potential impacts to individual species by overlaying future bird ranges with threats to calculate the proportion of species' ranges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 89 publications
1
22
0
Order By: Relevance
“…Hunting and birdwatching contribute millions of dollars per year to local economies (USFWS and U.S. Census Bureau 2016) and declines in wintering populations of dabbling and diving ducks in southern regions may lessen economic and cultural co-benefits (Guerry et al 2015). Our results provide additional support for concerns already expressed by duck hunters and waterfowl biologists (Vrtiska et al 2013, Moorman 2020, and forecasting studies (Bateman et al 2020) suggest continuation of the patterns documented by our analysis. Waterfowl hunting regulations have evolved in North America since enactment of the Migratory Bird Treaty Act in 1918 and will continue to evolve via strategic variations in adaptive harvest management (Nichols et al 1995).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Hunting and birdwatching contribute millions of dollars per year to local economies (USFWS and U.S. Census Bureau 2016) and declines in wintering populations of dabbling and diving ducks in southern regions may lessen economic and cultural co-benefits (Guerry et al 2015). Our results provide additional support for concerns already expressed by duck hunters and waterfowl biologists (Vrtiska et al 2013, Moorman 2020, and forecasting studies (Bateman et al 2020) suggest continuation of the patterns documented by our analysis. Waterfowl hunting regulations have evolved in North America since enactment of the Migratory Bird Treaty Act in 1918 and will continue to evolve via strategic variations in adaptive harvest management (Nichols et al 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Results from our study also complement another largescale study that predicted future changes in duck winter ranges with global warming (https://www.audubon.org/ climate/survivalbydegrees, accessed 24 Aug 2020). Bateman et al (2020) inferred that historical changes in winter ranges suggested by our study are expected to continue. Their projections indicated that, given a 3°C increase in global annual temperature, all species included in our study will continue the shift to wintering in historically colder regions at more northern latitudes.…”
Section: Discussionmentioning
confidence: 50%
“…The North American boreal biome is a mosaic of wetland complexes and forests that are projected to be transformed as the Earth's climate continues to warm and increase the frequency and magnitude of boreal disturbances such as drought, permafrost thaw, fire, and insect outbreaks [122]. Under various simulations of climate-mediated ecological change over the 21 st century, the boreal biome is projected to contract by up to 42% [123], and boreal birds are projected to both dramatically shift their ranges northwards and upwards in elevation and suffer disproportionately high losses in population size and range extent among North America avifauna [22,89,122,124,125]. The rusty blackbird is particularly vulnerable to projected reductions in suitable breeding habitat, which could result in the loss of more than half of the species' breeding range [125] and population numbers [89].…”
Section: Discussionmentioning
confidence: 99%
“…The North American boreal biome is a mosaic of wetland complexes and forests that are projected to be transformed as the Earth's climate continues to warm and increase the frequency and magnitude of boreal disturbances such as drought, permafrost thaw, fire, and insect outbreaks [122]. Under various simulations of climate-mediated ecological change over the 21 st century, the boreal biome is projected to contract by up to 42% [123], and boreal birds are projected to both dramatically shift their ranges northwards and upwards in elevation and suffer disproportionately high losses in population size and range extent among North America avifauna [22,89,122,124,125]. The rusty blackbird is particularly vulnerable to projected reductions in suitable breeding habitat, which could result in the loss of more than half of the species' breeding range [125] and population numbers [89].…”
Section: Discussionmentioning
confidence: 99%